Of Technology for Production of Dairy Fruit Cocktail with The Use of Milk By-Passed Raw Materials - Madieva Gulbahor Turdibaevna; Omonkeldieva Mastura Akbarali kizy (Zien Journals, 2021)
In the process of performing research work, original recipes for cocktails based on milk whey have been developed, technological modes of their production have been substantiated. The results of the studies showed that the obtained samples of cocktails in terms of organoleptic, physicochemical and microbiological indicators comply with the requirements of TR CU 033/2013 "On the safety of milk and dairy products"
Keywords: Microbiological; studies; process; organoleptic